Don Quijote . Don Quixote - Pabst, Georg Wilhelm (Germany, 1932)
Duration: 01:22:00 The French version of G.W.Pabst's monumental three-language (English, French and German - separate versions each) filming of Cervantes' classic novel. Pabst adaptation is starrring Russia's legendary opera singer, Fedor Shaliapin as Don Quixote.